ONE- STEP COMPARED WITH TWO-STEP GESTATIONAL DIABETES SCREENING AND PREGNANCY OUTCOMES : A SYSTEMATIC REVIEW - Putri Nurfauzia, Yunike (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Carbohydrate disorders, including gestational diabetes mellitus (GDM) and pregestational diabetes, have significant impacts on maternal, fetal, and neonatal health. Aim: This study aims to conduct a systematic review and analyze pooled data to evaluate how the choice of GDM testing strategy influences pregnancy outcomes. Methods: This systematic review adhered to the PRISMA guidelines. The study question and eligibility criteria were defined using the PICOT method, focusing on pregnant patients and comparing IADPSG one-step to Carpenter-Coustan two-step testing in the late mid-trimester Results: Three randomized controlled trials (RCTs) were included, involving a total of 2,333 participants. The one-step approach demonstrated a non-significant difference in GDM incidence compared to the two-step approach. However, the one-step approach was associated with significantly improved maternal and perinatal outcomes Conclusion: This systematic review provides insights into the comparison of One Step versus Two Step approaches for gestational diabetes screening and their impact on maternal and perinatal outcomes. While the incidence of GDM did not significantly differ between the two approaches